Strategy process : shaping the contours of the field - Chakravarthy, Bala.; Strategic Management Society; Blackwell Reference Online (Online service) ([Malden, MA] : Blackwell Pub., 2003)
"The framework offered in the book provides a basis for the continuous refinement of the field's research agenda. It has been shared with strategy process researchers and practitioners at the Strategic Management Society's meetings and mini-conference on strategy process research. The book itself comprises nine papers written by North American and European scholars, and is clustered into four streams that follow from the framework: chapters that track strategy content longitudinally; chapters that study the impact of important strategy process elements on performance; chapters that study the links between a firm's context and process elements; and chapters that seek to study context/process/outcomes."
"The editors provide a commentary on the strengths and weaknesses of each stream."--Jacket
Defining the contours of the strategy process field / Bala Chakravarthy [and others] -- Transforming the firm through the co-evolution of resources and scope / Alvaro Cuervo-Cazurra -- Change in the presence of fit : the rise, the fall, and the renaissance of Liz Claiborne / Nicolaj Siggelkow -- Resources, management systems, and governance : keys to value creation / Karen Schnatterly, Catherine Maritan -- The essence of process : effective strategic planning in practice / John C. Camillus -- A multilevel analysis of the strategic decision process and the evolution of shared beliefs / Mirela Schwarz -- The social construction of organizational capabilities : a multi-level analysis / V.K. Narayanan [and others] -- The conditioning and knowledge creating view : managing strategic initiatives in large firms / Martin W. Wielemaker [and others] -- A longitudinal study of organizational learning, unlearning and innovation among IJVs in a transitional economy / Marjorie Lyles [and others] -- Strategic renewal processes in multi-unit firms : generic journeys of change / Henk W. Volberda, Charles W.F. Baden-Fuller -- Shaping, implementing, and changing strategy : opportunities and challenges / Bala Chakravarthy [and others].
Revised papers presented at Strategic Management Society meetings.
Includes bibliographical references and index.
English.
John Wiley and Sons
Keywords: Strategic planning -- Congresses; v; Strategic planning; Strategisch management; Strategische planning; Conference papers and proceedings